The Effectiveness of the Mind Mapping Model Assisted by Microsoft Sway Media on Social Studies Learning Outcomes - Isma Salsabila Prasetyowati; Novi Setyasto (Jurnal Pendidikan dan Pengajaran, 2023)
The use of learning models and media that are outside the 2013 curriculum has an impact on the low learning outcomes of students. This study aims to test the effectiveness of the Mind Mapping learning model assisted by Microsoft Sway media on social studies learning outcomes. This study used a quantitative experimental approach with a Pretest-Posttest Control Group Design. The population in this study was 116 students in the fifth grade of elementary school. The sampling technique used was purposive sampling involving 60 students, 30 students in the experimental and 30 in the control classes—data collection techniques with observation, interviews, and documentation. Data analysis techniques include initial data analysis by normality and homogeneity tests and final data analysis by t-test and N-Gain tests. The t-test results obtained a sig value of 0.004, less than 0.05. So that Ho is rejected and Ha is accepted. It is supported by the results of the N-Gain test for the experimental class of 0.418 and the control class of 0.260. The Mind Mapping learning model assisted by Microsoft Sway media is more effective in increasing the activity and learning outcomes of students in social studies subjects in fifth-grade elementary schools.